Functional nanoparticles in electrospun fibers for biomedical applications. Issue 6 (16th December 2021) - Saiding, Qimanguli; Cui, Wenguo
Abstract: Electrospinning provides a facile route for generating fibers with diameters ranging from hundreds of nanometers to several micrometers. This technology has been widely explored in many biomedical areas including drug delivery systems (DDS), disease diagnosis and treatment, biosensing as well as tissue engineering. However, there are still existing challenges for electrospinning fibers in achieving complex regenerative or reconstructive processes through pure surface modification or simple drug loading. With the rise of nanotechnology, functional nanoparticles (NPs) made by various materials rapidly emerged in tissue engineering and regenerative medicine. Due to the objective size difference between NPs and electrospun fibers, doping NPs into electrospun nanofibers makes it possible to produce functional fibers having the inherent merits of both the guest NPs and the host fibers. In this review, we focus on the recent progress in preparing nanoparticle bearing electrospun hybrid fibers for biomedical applications. The organic, inorganic and mesoporous nanoparticles combined with electrospun nanofibers for different biological scenarios with several notable examples were systematically reviewed. Then, we finish with challenges and future perspectives of electrospun hybrid fiber materials for drug delivery and regenerative medicine. Abstract : Functional nanoparticles (NPs) incorporated electrospun hybrid fibers prepared by blending, stacking, wrapping or coating methods were summarized. Metallic NPs, silica based mesoporous NPs, liposomes, and polymer NPs in electrospun fibers in anticancer, antibacterial, osteogenesis, vascularization, biosensing and gene delivery applications was systematically reviewed with existing challenges and future prospects. NPs in electrospun fibers strategy provide a new horizon for biomaterial design and development in tissue engineering and regenerative medicine.